Assessment of Lobster Fisheries and Sustainable Management Strategies: A Case Study of EAFM in Central Lombok – Indonesia. Issue 1 (May 2021) - Hilyana, Sitti; Buhari, Nurliah; Gigentika, Soraya; Amir, Sadikin; Waspodo, Saptono; Himawan, Mahardika R.; Jefri, Edwin
Abstract: The exploitation of lobster resources in the waters of the Central Lombok Regency, Indonesia is not effectively managed, causing problems in terms of resource availability and sustainability of lobster fishing operations. This study aimed to assess the status of lobster fisheries management and policy strategies for sustainable lobster fisheries management. Data were collected in three lobster fishing centres: Teluk Awang, Teluk Bumbang and Teluk Gerupuk. Methods used were a structured interview technique with questionnaires, focus group discussions (FGDs) and public consultation. The status of the lobster fishery was analysed using the Ecosystem Approach to Fisheries Management (EAFM) indicators with six Domains. The lobster fishery management status was classified as "moderate" (aggregate score 50/100). The Fisheries Resources Domain scored 35, indicating that lobster stocks are in "poor" condition. Four dimensions had a "moderate" status: the Fisheries Technology Dimension (43), the Economic Dimension (48), the Social Dimension (53), and the institutional dimension (55). The Habitat and Ecosystem Dimensions was classified as "good" (67). Sustainable lobster fisheries management strategies include regulating fishing quotas, banning gears which catch lobster seed, and optimizing the use of selective fishing gear; establishing a working group for lobster management; managing water quality and zonation of lobster habitat; transfer of lobster farming techniques; and empowering community coastwatch groups.